Ravenous : Otto Warburg, the Nazis, and the search for the cancer-diet connection - Apple, Sam (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2021)
"The extraordinary story of the Nazi-era scientific genius who discovered how cancer cells eat-and what it means for how we should. The Nobel laureate Otto Warburg-a cousin of the famous finance Warburgs-was widely regarded in his day as one of the most important biochemists of the twentieth century, a man whose research was integral to humanity's understanding of cancer. He was also among the most despised figures in Nazi Germany. As a Jewish homosexual living openly with his male partner, Warburg represented all that the Third Reich abhorred. Yet Hitler and his top advisors dreaded cancer, and protected Warburg in the hope that he could cure it"--